Applications of Pulsed Electromagnetic Field Therapy in Skeletal-Muscle System: An Integrative Review - Leonardo, Patrícia Sardinha; Cardoso, Katielle Rodrigues da Silva; Vieira, Rodolfo de Paula; Ruiz-Silva, Carlos; Coelho, Carly de Faria; Martins, Pedro Sardinha Leonardo Lopes; Lopes-Martins, Rodrigo Alvaro Brandão (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: The Pulsed Electromagnetic Field (PEMF) technology has attracted increasing interest since consistent evidence of its therapeutic properties has been demonstrated to treat musculoskeletal conditions. However, this technology is not new, and has already been used in different experimental models and clinical studies for the treatment of tendinopathies, osteoarthritis, increased cell proliferation, bone consolidation, among others. Methods: In this work, we carried out an integrative review of clinical and experimental studies published in the last twenty years, on the available scientific evidence that demonstrate the effects of PEMF in different applications for health treatments. Five databases including Medline, Pubmed Central, Scopus, Lilacs and PEDro were searched for studies from 2001 to September 2022. The results were analyzed by the team of researchers and clinical professionals to assure methodological quality of the studies for the elaboration of the theoretical review on the effects of electromagnetic field stimulation on skeletal muscles, tendon or bones. Results: Sixty-two studies were included in this review, presenting evidence of the biological effects of PEMF that can suggest it´s possible use to treat different disorders. Conclusions: Pulsed electromagnetic fields (PEMF) present relevant clinical and experimental evidence of beneficial effects in the treatment of several musculoskeletal inflammatory disorders, such as tendinopathies and osteoarthritis, in addition to the treatment of urinary incontinence and abdominal diastasis. PEMF can be considered as the evolution of electrical currents for the treatment of musculoskeletal disorders, mainly due to its better tolerance by patients.